Language Acquisition Concerning Intercultural and International Dialogue - Dr. Abdulaziz Alshahrani (Journal of Arts, Literature, Humanities and Social Sciences, 2023)
This paper aimed to systematically review the literature on language acquisition concerning intercultural and international dialogue. Using Google Scholar and PRISMA screening, 27 papers could be selected for this review. Due to the inherent and inseparable nature of culture with language, learning language alone will not achieve intercultural awareness, essential for intercultural and international dialogue. Second Language Acquisition theory needs to be integrated with the dialogue theory of Bhaktin and operationalised through Byram’s intercultural citizenship theory using tools such as telecollaboration for the effective development of both language and intercultural awareness for intercultural and international dialogue. From a practical standpoint, the most appropriate way to build competency in the language-culture nexus is to raise awareness of both language and intercultural aspects; this can lead to effective intercultural and international dialogue.